The population genomics of Conyza spp. in soybean macroregions suggest the spread of herbicide resistance through intraspecific and interspecific gene flow - Kalsing, Augusto [UNESP]; Velini, Edivaldo D. [UNESP]; Merotto, Aldo; Carbonari, Caio A. [UNESP] (Springer Nature, 2024)
Herbicide-resistant Conyza spp. are a threat to many crops. These widespread weeds are closely related species and often cooccur. To characterize the origins of their resistance and the mechanisms underlying their spread, we assessed the genomic variation in glyphosate-resistant Conyza spp. in Brazil. Twenty populations were sampled from soybean fields across four macroregions (MRSs). A genotyping-by-sequencing study resulted in 2,998 single-nucleotide polymorphisms (SNPs) obtained for C. bonariensis (L.) and the closely related C. sumatrensis (Retz) E. Walker. Higher genomic diversity (π) and heterozygosity (HO/HE) and lower inbreeding coefficient (FIS) values were detected in populations of Conyza spp. from MRS 1 (southern) than in those from other MRSs. Strong genomic structure clustered individuals into three groups (FST = 0.22; p value = 0.000) associated with the MRSs. Thus, resistance to glyphosate originated from independent selection in different MRSs across Brazil. Our dataset supports the occurrence of intraspecific gene flow in Brazil and identified individuals of C. bonariensis that did not group within species. These findings suggest that allelic introgressions within and among species have impacted the evolution and spread of resistance to glyphosate in Conyza spp. We discuss how to mitigate new resistance cases, particularly for the released stacked traits herbicide tolerance in soybeans.